Nganyareh Kabin Practices in Jukong Village: A Phenomenological Theory Perspective from Alfred Schutz (Case Study in Jukong Village, Labang District, Bangkalan Regency) - Famirotul Lail; Umi Sumbulah; Badruddin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study analyzes the practice of Nganyareh Kabin a local term in Jukong Village, Labang District, Bangkalan Regency, for the renewal of a marriage contract, or Tajdid an-Nikah performed by married couples in a legally valid marriage. This study uses a qualitative approach with Alfred Schutz's Phenomenological theoretical framework to understand the subjective meaning of this social act from the perspective of the participants. In practice, Nganyareh Kabin is conducted very simply, privately, and secretly, without a wedding reception or crowd, attended only by the husband, wife, guardian, witnesses, and religious figures (kiai or modin). Despite its private nature, this process ensures the fulfillment of all the pillars and requirements of Islamic law, emphasizing the couple's careful attitude (ihtiyath) to ensure the legitimacy of their renewed bond. The main findings indicate that the participants' motivations are divided into two phenomenological dimensions: the